A Christmas home - Perry, Marta (A Promise Glenn novel, 2019)
After ten years spent keeping house and raising her younger siblings, Sarah Yoder returns home to Promise Glen determined to make a fresh start. Her new job with neighbor Noah Raber's furniture business seems promising<U+2014>until she and the woodworker clash over everything from the best way to reach new costumers to how to raise his mischievous six-year-old twin boys. Though Sarah longs for a home of her own, she fights the appeal of this ready-made family, resolved to maintain a professional distance. But when she and Noah both agree to help with the school's annual Christmas program, Sarah finds her heart touched by the motherless boys and Noah's quiet strength. Thrown together at work and at the school, their feelings continue to grow, and Sarah struggles to keep Noah at arms' length. Loving Noah may seem impossible, but with faith, love, and a little help from their close-knit community, there may yet be a Christmas home for them both.